2008
DOI: 10.1016/j.ydbio.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of retinal vascular development and neovascularization in PECAM-1-deficient mice

Abstract: Platelet-endothelial cell adhesion molecule-1 (PECAM-1/CD31) is expressed on the surface of endothelial cells (EC) at high levels with important roles in angiogenesis and inflammation. However, the physiological role PECAM-1 plays during vascular development and angiogenesis remains largely unknown. Here we determined the role of PECAM-1 in the postnatal development of retinal vasculature and retinal neovascularization during oxygen-induced ischemic retinopathy (OIR) using PECAM-1-deficient (PECAM-1-/-) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 47 publications
7
39
1
Order By: Relevance
“…32), high expression of thrombospondin 1 might at least in part represent a molecular mechanism of the anti-angiogenic action upon the loss of Wt1. The direct transcriptional activation of Pecam-1 by Wt1, which we report here, is in agreement with decreased Pecam-1 expression and reduced angiogenesis and increased endothelial cell apoptosis in tumours of Wt1 KO mice 44 . Overexpression of Pecam-1 in mouse endothelial cells knocked down for Wt1 expression partially rescued the impaired tube formation of these cells.…”
Section: Discussionsupporting
confidence: 91%
“…32), high expression of thrombospondin 1 might at least in part represent a molecular mechanism of the anti-angiogenic action upon the loss of Wt1. The direct transcriptional activation of Pecam-1 by Wt1, which we report here, is in agreement with decreased Pecam-1 expression and reduced angiogenesis and increased endothelial cell apoptosis in tumours of Wt1 KO mice 44 . Overexpression of Pecam-1 in mouse endothelial cells knocked down for Wt1 expression partially rescued the impaired tube formation of these cells.…”
Section: Discussionsupporting
confidence: 91%
“…Although studies in mice have demonstrated that CD31 deficiency can be compensated by CD31-independent pathways during development [49], other research, which is consistent with our studies, has shown that CD31 antibodies or deficiency can block endothelial-endothelial interactions and the formation of endothelial tubules in Matrigel assays in vitro, as well as angiogenesis in in vivo murine models [48,50,51]. CD31/ PECAM-1 on endothelial cells also contributes to vascular barrier integrity [52] and arteriogenesis [53], to endothelial cell function required for alveolarization [50], and to enhanced retinal vascular density in postnatal mice when comparisons are made with PECAM-1-deficient mice [54]. Of further note, we observed that CD105/endoglin remained unaltered on ECFC-derived cells after AMD3100 treatment and this would be consistent with the regulation of CD105 function by BMP9 [55].…”
Section: Discussionmentioning
confidence: 58%
“…Reduced migration, inability to undergo capillary morphogenesis in matrigel (Kondo et al, 2007) Total Mice viable, defects in retinal vasculature (Dimaio et al, 2008) β-catenin Cell-cell adhesion Conditional EC-specific knockout Death between E11.5 and E13.5; impaired vascular patterning in the head, vitelline and umbilical vessels, and placenta (Cattelino et al, 2003) N-cadherin Cell-cell adhesion Conditional NC specific Defects in remodeling of cardiac outflow tract (Luo et al, 2006) Total Death by E10 (Radice et al, 1997) Conditional EC specific Death at midgestation, severe vascular defects, decrease of VE-cadherin (Luo and Radice, 2005) E-cadherin Cell-cell adhesion Total Early lethality, fail to form trophectoderm. (Larue et al, 1994) VE-cadherin Cell-cell adhesion Total Death at E9.5, endothelial cells are assembled in vascular plexi, but their subsequent remodeling and maturation are impaired.…”
Section: Note On Nomenclaturementioning
confidence: 99%